Beyond satisfaction: evaluating understanding in PICU family centered rounds. (2nd October 2022) - Edwell, April; Schaik, Sandrijn van; Desai, Mansi
ABSTRACT: Background: Many hospitals have adopted Family Centered Rounds (FCR), as a means to optimize communication. While studies show FCR improves family satisfaction, research on the impact on family understanding of their child's care has been conflicting. Understanding is particularly important when families are asked to share in complex decision making, as occurs in the Pediatric Intensive Care Unit (PICU). This study explores families' experiences of FCR in the PICU and examines how FCR impacts their understanding of their child's care. Methods: We conducted surveys and interviews of family members after they attended FCR in two PICUs. The survey assessed families' satisfaction with rounds and their understanding across three domains: the child's illness, treatments, and prognosis. Physicians completed a similar survey to examine concordance with families' understanding. In interviews we explored underlying factors. We identified themes from transcripts through thematic analysis. Results: Twenty-five family members completed the survey and participated in interviews. The majority (82%) rated their satisfaction with FCR highly. Discordance between families and physicians in understanding was common, especially in the prognosis domain, with concordance rates as low as 27%. We identified four themes from interviews that shed light on families' experiences and the relationship between FCR and understanding: Jargon, Feeling Part of the Team, Rounds as Overwhelming and Competing Purposes of Rounds. Conclusion: Families in our study had similar satisfaction with FCR as previously reported, yet our findings suggest that FCR can be optimized to achieve family understanding. Our findings provide insights into potential ways to accomplish this.